KRIMINALISASI KEBIJAKAN PEJABAT PUBLIK DALAM HUKUM PIDANA - Mutalib, Abdul (UIR Press, 2023)
This article aims to discuss how to solve the criminalization of public official policies. In the context of democratization, public official policies are seen as a process of accommodating the wishes of various stakeholders in society, the environment as a legally binding and enforced product. This is where law becomes very important to discuss its contextuality, especially in relation to the policies of public officials as an instrument of society. This paper tries to review a little about the criminalization of public official policies in criminal law. The method used by normative by the conceptual approach, which examines the problem of the vision of legal reform related to the criminalization of public official policies, which is based on theoretical studies and doctrines. legal experts, that can be convicted and held accountable, such as responsibility in the concept of criminal law.